Stress Intensity Factors for Corner Cracks under Arbitrary Stress Fields in the Finite Plates Based on the Point Weight Function Method - Guo Li; Huimin Zhou; Junbo Liu; Tongge Xu; Shuiting Ding (International Journal of Aerospace Engineering)
Probabilistic damage tolerance assessment is an essential method to evaluate the safety of aeroengine rotors. The stress intensity factors (SIFs) are the core parameters. The weight function method can calculate SIF efficiently. The available weight functions for corner cracks are suitable for cracks with universal stresses. However, when cracks are under bivariant stress distributions, the lack of the weight function database makes the damage tolerance assessment impractical. Therefore, this paper derives the point weight functions for corner cracks, which are suited for cracks in real-world components with two-directional stress distributions. The response surface method is used to build the surrogate model of the point weight functions. By integrating the weight functions with the stress distributions, SIFs can be calculated with high accuracy. In sum, 81% of the differences between the point weight function method and finite element results are less than 10%.